Efikasi diri dan Dukungan Sosial Keluarga Terhadap Pengambilan Keputusan Karir Siswa Sekolah Menengah Atas: Sebuah Studi Systematic Literature Review - Soraya, Kamila; Hidayat , Dede Rahmat; Badrujaman, Aip (Institut Agama Islam Daruttaqwa Gresik, 2025)
Self-Efficacy in career decision making is an individual's belief that he or she is able to complete tasks related to career decision making. Then family social support becomes one of the obstacles for students in making career decisions. In previous studies, many studies conducted analyses related to Self-Efficacy and family social support with students' career decision making focusing on correlational research and case studies. However, there is still a lack of research using the Systematic Literature Review (SLR). This study aims to determine the effect of the Self-Efficacy variable on career decision making through the SLR method. This study uses the Systematic Literature Review method by reviewing articles from 2020-2025 published in Google Scholar, PubMed, and Semantic Scholar. The research design uses the Preferred Reporting Items for Systematic Literature Reviews and Meta-Analysis (PRISMA) guidelines. The results of the study showed that self-efficacy and family social support have a positive contribution to students' career decision making. Increasing self-efficacy and family support can improve students' career decision-making abilities. Students' self-confidence in their ability to understand the concept of career decision making will determine how well they understand the concept.